2013 IEEE Grenoble Conference 2013
DOI: 10.1109/ptc.2013.6652427
|View full text |Cite
|
Sign up to set email alerts
|

A redundancy optimization model applied to offshore wind turbine power converters

Abstract: Unexpected failures, high operation and maintenance (O&M) cost, and low accessibility are critical issues for offshore wind farms. According to existing statistics, power converters are among the most critical components in offshore wind turbines, and suffer from a high failure rate. One efficient way to improve the reliability and availability of the converter system is by adding at least one independent redundant converter, which ensures that the system would still operate in case of a converter failure. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Our failure data has been collected from ten-minute Supervisory control and data acquisition (SCADA) database, automated fault logs, O&M reports, and supplemented with data from references [11,[29][30][31]. Figure 5 represents the failure rate of the sixteen sub-assemblies of the onshore/offshore wind turbine system.…”
Section: A Comparative Studymentioning
confidence: 99%
“…Our failure data has been collected from ten-minute Supervisory control and data acquisition (SCADA) database, automated fault logs, O&M reports, and supplemented with data from references [11,[29][30][31]. Figure 5 represents the failure rate of the sixteen sub-assemblies of the onshore/offshore wind turbine system.…”
Section: A Comparative Studymentioning
confidence: 99%
“…5 This paper proposes an approach of joint redundancy and maintenance strategy optimization for offshore power converters which extends the model presented in our study in Ref. 6. We in particular aim to simultaneously determine the optimal allocation of redundant converters and the optimal threshold number of converters that are allowed to fail before sending a maintenance crew to the offshore platform.…”
Section: Introductionmentioning
confidence: 86%
“…A new approach that can be taken by industry is rethinking the design of the turbines, and the way in which the wind turbine units could be simplified in order to reduce maintenance costs and increase the reliability of the system is described in [41,111]. Simplifying multiple power converters in each turbine would be [44] a possible benefit, including cost savings, loss and maintenance reduction and increased system reliability, however, Shafiee et al [112] proposed an effective way to improve the reliability and availability of the converter system by adding at least one independent redundant converter in offshore wind farms, which ensures that the system will work in case of a converter failure. It can save a great deal of maintenance of offshore turbines with optimal [113] generator designs, and the fixed-pitch fixed-speed induction generator-based wind turbine presents low [114] maintenance costs in [115], and the results confirmed that the controllability of the wind farm is increased using a rotor impedance control technique.…”
Section: Maintenance and Life Cycle Cost (M_cost)mentioning
confidence: 99%